Power transmissions : Proceedings of the 4th International Conference, held at Sinaia, Romania, June 20 -23, 2012 - Dobre, George (Mechanisms and Machine Science, 2013)
This books contains the Proceedings of the 4th International Conference on Power Transmissions, that was held in Sinaia, Romania from June 20 -23, 2012. Power Transmissions is a very complex and multi-disciplinary scientific field of Mechanical Engineering that covers the different types of transmissions (mechanical, hydraulic, pneumatic) as well as all the machine elements involved, such as gears, bearings, shafts, couplings and a lot more. It concerns not only their basic theory but also their design, analysis, testing, application and maintenance. The requirements set to modern power transmissions are really tough to meet: They need to be more efficient, stronger, smaller, noiseless, easier to produce and to cost less. There is a strong demand to become easier in operation and maintenance, or even automatic and in maintenance-free. Last but not least, they should be easily recycled and respect the environment. Joint efforts of specialists from both academia and industry can significantly contribute to fulfill these needs. The main goal of this conference was to bring together experts from all over the world and present the latest developments in the field of Power Transmissions.